Aberrant Super‐Enhancer Landscape in Human Hepatocellular Carcinoma - Tsang, Felice Ho‐Ching; Law, Cheuk‐Ting; Tang, Tsz‐Ching Chloe; Cheng, Carol Lai‐Hung; Chin, Don Wai‐Ching; Tam, Wing‐Sum Vincy; Wei, Lai; Wong, Carmen Chak‐Lui; Ng, Irene Oi‐Lin; Wong, Chun‐Ming (Hepatology (Baltimore, Md.), 2019)
Hepatocellular carcinoma (HCC) cells exploit an aberrant transcriptional program to sustain their infinite growth and progression. Emerging evidence indicates that the continuous and robust transcription of oncogenes in cancer cells is often driven by super‐enhancers (SEs). In this study, we systematically compared the SE landscapes between normal liver and HCC cells and revealed that the cis‐acting SE landscape was extensively reprogrammed during liver carcinogenesis. HCC cells acquired SEs at multiple prominent oncogenes to drive their vigorous expression. We identified sphingosine kinase 1 (SPHK1) as an SE‐associated oncogene, and we used this gene as an example to illustrate the impact of SEs on the activation of oncogenes in HCC. Concurrently, we also showed that the critical components of the trans‐acting SE complex, namely, cyclin‐dependent kinase 7 (CDK7), bromodomain‐containing protein 4 (BRD4), E1A binding protein P300 (EP300), and mediator complex subunit 1 (MED1), were frequently overexpressed in human HCCs and were associated with the poor prognosis of patients with HCC. Using the CRISPR/Cas9 gene‐editing system and specific small‐molecule inhibitors, we further demonstrated that HCC cells were highly sensitive to perturbations of the SE complex. The inactivation of CDK7, BRD4, EP300, and MED1 selectively repressed the expression of SE‐associated oncogenes in HCC. Finally, we demonstrated that THZ1, which is a small‐molecule inhibitor of CDK7, exerted a prominent anticancer effect in both in vitro and in vivo HCC models. Conclusion: The SE landscape and machinery were significantly altered in human HCCs. HCC cells are highly susceptible to perturbations of the SE complex due to the resulting selective suppression of SE‐associated oncogenes. Our results suggest that targeting SE complex is a promising therapeutic strategy for HCC treatment.